Company Growth and Profitability in Corporate Value with Environmental Disclosure as a Moderation in Oil, Gas and Coal Companies - Putri, Ika Swasti; Bambang Sutopo (Politeknik Ganesha Medan, 2024)
This study examines the relationship between company growth, profitability, and corporate value, focusing on the role of environmental disclosure as a moderation variable in the oil, gas, and coal sectors. Using data from 15 companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2022, this study applies multiple linear regression analysis to test hypotheses related to the effect of growth and profitability on company value, as well as how environmental disclosures moderate these relationships. The results show that profitability significantly affects the value of the company, confirming that more profitable companies tend to be valued higher in the market. Environmental disclosure also has a significant impact on corporate value, emphasizing the importance of transparency and environmental responsibility. While company growth has no significant relationship with firm value, the interaction between profitability and environmental disclosure to company value is significant, suggesting that the positive effects of environmental disclosure are amplified by firm profitability. These findings offer important insights for stakeholders in making investment decisions and environmentally sound business practices.